A Design Consideration for Planar Inverted Fractal Antenna to Minimize Length-Dependent Specific Absorption Rate - Akramul Haque; Sheikh Alimur Razi; Nur Mohammad; Md. Shamsul Arifin; Quazi Delwar Hossain (Institute of Advanced Engineering and Science, 2018)
This paper presents a numerical solution to minimize electromagnetic radiation from a Planar Inverted Fractal Antenna (PIFA) used in cellular phone. The PIFA is simulated using a semiconductor substrate having a dielectric constant of 3.38. The height of the dielectric substrate is 0.813 mm. The designed antenna is simulated at a broad range of microwave frequency spectrum used in cellular communication. A 50-ohm probe of 0.5 mm radius perpendicular to the ground substrate plate is used as a feeding medium. The antenna performance is evaluated for three different lengths keeping all other parameters constant. Simulation results show that the intended PIFA having a length of 20 mm can be used effectively to reduce the Specific Absorption Rate (SAR) of radiation. Moreover, the reflection coefficient was found to be minimal 0.1569 at 20 mm antenna length which is determined by characteristic impedance relation. Therefore, this investigation of minimizing the radiation absorption can be considered during the implementation phase of various cellular antennas to avoid radiation-related health hazards.